EKSISTENSI ASAS KESEIMBANGAN DALAM KONTRAK KERJA SAMA PENANAMAN MODAL - Septia Ningsih, Kadek; Dharmakusuma, A A Gede Agung; Dewi Kasih, Desak Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
In succeeding national development program in Indonesia, one effort performed by the Government is by providing opportunity for foreign investors to invest in Indonesia. Besides using other efforts such as the use of foreign assistances, the existence of corporation in building businesses is badly needed for the sake of the business performance such as in the form of foreign investment in which the development of corporation between foreign parties and both government and private sectors in Indonesia is very important in particular with transferring technology and skill.
Keywords: Equilibrium Principle, Foreign Investment Contract.